All-organic dielectric polymer films exhibiting superior electric breakdown strength and discharged energy density by adjusting the electrode–dielectric interface with an organic nano-interlayer. Issue 10 (13th September 2021) - Pei, Jia-Yao; Zhong, Shao-Long; Zhao, Yu; Yin, Li-Juan; Feng, Qi-Kun; Huang, Lei; Liu, Di-Fan; Zhang, Yong-Xin; Dang, Zhi-Min
Abstract : The surface morphology of dielectric films has a great effect on the insulation performance. Remarkably improved capacitive performance is realized by adjusting the electrode–dielectric interface. Abstract : Polymer dielectrics for energy storage applications usually endure high electric field strength. Adjustment of the composition and structure of the dielectric bulk phase to enhance the dielectric breakdown strength has been widely studied. However, the effect of electrode–dielectric interface on the breakdown strength has received little attention, which greatly hinders further development in this field. In this work, an all-organic double-layer dielectric film consisting of poly(vinylidene fluoride) (PVDF) as the matrix and polymethyl methacrylate (PMMA) as the organic nano-interlayer was prepared. By adjusting the electrode–dielectric interface, remarkably improved electric breakdown strength (767.05 MV m −1 ) and discharged energy density (19.08 J cm −3 ) were realized concurrently without sacrificing the charge–discharge efficiency. The experimental results and computational simulations reveal that the surface morphology of dielectrics has a great effect on the electric field distribution at the electrode–dielectric interface, and further affects the leakage current and breakdown strength of the dielectric. The PMMA nano-interlayer modifies the surface defects and increases the Young's modulus at the electrode–dielectric interface, leading to the improvement of insulation performance. These findings offer a new perspective to understand the impact of the electrode–dielectric interface on the polymer dielectric breakdown strength. This work provides a novel paradigm for fabricating polymer dielectrics with high breakdown strength for energy storage.